Le droit de la preuve et la pétition en contestation d'élection - Morin, Jacques Carl (Les Cahiers de droit, 1979)
Evidence in the law of controverted elections is the subject of the present article. The author begins with some general observations. Firstly, according to section 52 of the provincial Controverted Elections Act, the rules of evidence are those of the law of England in force on the first of July 1867, or in other words, the common law of Parliament. These rules of evidence can hardly be of any assistance to our courts because at that time, disputed elections were tried by the House of Commons or its committees and decided in a thoroughly unjudicial manner. Secondly, the author describes briefly the grounds that may be alleged in an election petition, namely the ineligibility of the elected candidate, corrupt practices by the candidate and irregularities affecting the legality of the election. In the first part, the author examines the burden of proof. In all cases the onus for establishing the material fact of the corrupt practices or the noncompliance with the rules contained in the Election Act rests upon the petitioner. If the corrupt practices alleged in the petition are substantiated, the court must set aside the election unless the respondent establishes that the action is of no gravity and could not have affected the result of the election. On the other hand, an election will not be declared void by reason of transgressions of the law if the court is satisfied that it was conducted in accordance with the existing election law, and that the mistake or noncompliance did not affect the outcome of the election. The second part discusses the method of establishing facts and proof of their possible effect on the result of the election. As to presumption, for instance, the author examines the solution adopted by the courts when the number of unqualified voters exceeds the majority of the elected candidate and finds that invalidation of such an election may not be always justified. Finally, in the third part, the author analyses various clauses regarding the secrecy of the ballot. In federal law and in the law of the English-speaking provinces the privilege respecting the secrecy of the vote is judicially recognized and cannot be waived. In Quebec, a voter cannot be compelled to reveal for whom he has voted but he can be asked the question. In the United States, the privilege of non-disclosure belongs only to qualified voters, and the illegal voter can be compelled to disclose for whom he has voted. Rules of evidence regarding controverted elections are not well adapted to our times ; furthermore some sections of the ElectionAct and the Controverted Elections Act are not understood by our courts. The legislator should modify these statutes and make their language more precise in order to achieve completely and successfully the electoral reform now in progress.